Knowledge, Attitude, Sexual Behavior, Family Support, and Their Associations with HIV/AIDS Status in Housewives - Budi Laksana; Argyo Demartoto; Dono Indarto (Masters Program in Public Health, 2017)
Background: Approximately 36.7 million people in the world were infected by HIV and 2.1 million new cases occured in 2015. A total of 191,073 HIV cases were reported in Indonesia in 2016, including 77,940 AIDS cases, and 13,247 deaths. Housewives ranked highest among HIV/AIDS patients in Indonesia. This study aimed to investigate knowledge, attitude, sexual behavior, family support, and their associations with HIV status in housewives using PRECEDE PROCEED model.Subjects and Method: This was an analytic observational study with cross-sectional design. The study was conducted at Toroh community health center, Grobogan, Central Java, in July, 2017. A total sample of 129 housewives were selected for this study using exhaustive sampling technique. The dependent variable was HIV status. The independent variables were knowledge, attitude, sexual behavior, and family support. The data was measured by a set of questionnaire and analyzed using path analysis.Results: HIV status was directly and positively associated with risky sexual behavior (b= 4.48; 95% CI= 2.30 to 6.65; p<0.001). Risky sexual behavior was associated with attitude (b= -1.27; 95% CI = -0.03 to -2.51; p<0.045) and family support (b= -1.86; 95% CI= -0.69 to -3.03; p<0.002). Attitude was associated with knowledge (b= 2.06; 95% CI = 0.86 to 3.25; p<0.001).Conclusion: HIV status is directly and positively associated with risky sexual behavior. HIV status is indirectly associated with attitude, knowledge, and family support.Keywords: HIV, AIDS, risky sexual behavior, housewives, PRECEDE PROCEED modelCorrespondence: Budi Laksana. Diploma III Program in Midwifery Muhammadiyah, Madiun, East Java. Email: lakortikosteroid@gmail.com. Mobile: +6285655612000.Journal of Epidemiology and Public Health (2017), 2(2): 154-163https://doi.org/10.26911/jepublichealth.2017.02.02.06